Longitudinal deformation of a third generation zotarolimus eluting stent:“The concertina returns.” - Panoulas, Vasileios F; Demir, Ozan M; Ruparelia, Neil; Malik, Iqbal (World journal of cardiology, 2017)
In the current case series we describe two cases of longitudinal stent deformation in ostial lesions treated with a new generation zotarolimus eluting stent and review current literature on longitudinal stent deformation. Historically not a common occurrence,longitudinal deformation occurred mainly in Promus Element everolimus eluting stents,which had only two rather than the commonly used 3 links between stent rings. Longitudinal deformation commonly occurs secondary to compression of the proximal edge of the stent by either the guide catheters,or intravascular balloons and imaging catheters. The degree of deformation however,depends on the longitudinal strength and design of the stent.